Meaning, manifestations, actors and causes of violence from young people’s perspective - Cortés, Maria de Lourdes (Consorcio de Universidades Mexicanas A.C., 2019)
An exploratory study was conducted with young people about the meaning they attribute to violence and his types, characteristics of the actors, victims and aggressors, the causes, consequences and possibilities of prevention. 22 people were selected through a non-probabilistic sampling of the city of Mérida, Yucatán, 10 men and 12 women, with an average age of 22.45 years and a standard deviation of 2.32. A structured interview was carried out consisting of 22 questions that explored knowledge and beliefs about interpersonal violence: a) Meaning (characterization, types, scenarios); b) Aggressors (characteristics, places where it occurs, causes to attack, possibility of helping them); c) Victims (characteristics, how to help victims) and d) Causes of violence, consequences, and prevention (how to prevent, what measures you know). The findings show limited knowledge about interpersonal violence, although they know different expressions of violence and some contexts in which it manifests itself. Likewise, it is observed that there are myths about the cause of the violence and the characteristics of the aggressors and victims, as well as about the possibility of preventing it. It is concluded that it is necessary to promote knowledge to reinforce and sensitize young people through different strategies to prevent any type of violence.